2019
DOI: 10.1080/1369183x.2019.1654155
|View full text |Cite
|
Sign up to set email alerts
|

Beyond being either-or: identification of multiracial and multiethnic Japanese

Abstract: Although the number of multiracial and multiethnic Japanese who are socially recognised and identified as haafu (mixed) has increased due to a rise in intermarriages, the identities and experiences of mixed persons in Japan are seldom critically analysed. Based on interviews with 29 multiracial and multiethnic individuals residing in Japan, this article explores not only how multiracial and multiethnic Japanese identify themselves but also how they feel they are identified by others in society. The analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…As a consequence, multiple generations of persistent challenges may be required to change levels of discrimination, and this time frame is corroborated by studies on immigrant integration, intermarriage or the perception of 'mixed' children where changes are measured in 'generations' (Alba, 2017;Rumbaut, 2008;Song, 2015;Törngren & Sato, 2019). Focusing on members of the minority groups, this literature also recognizes intermediary positions, where individuals can express loyalty and feel attached to both the minority and majority groups at the same time.…”
Section: How Discrimination (Can) Changementioning
confidence: 90%
“…As a consequence, multiple generations of persistent challenges may be required to change levels of discrimination, and this time frame is corroborated by studies on immigrant integration, intermarriage or the perception of 'mixed' children where changes are measured in 'generations' (Alba, 2017;Rumbaut, 2008;Song, 2015;Törngren & Sato, 2019). Focusing on members of the minority groups, this literature also recognizes intermediary positions, where individuals can express loyalty and feel attached to both the minority and majority groups at the same time.…”
Section: How Discrimination (Can) Changementioning
confidence: 90%
“…Being Eurasian in Singapore is explored by Rocha and Yeoh (2021) where they found that, "Mixed identities and identification are crucial, with inclusion and exclusion being strategic and positional, and identities increasingly recognized as complex and multiple, rather than simple and singular" (Rocha and Yeoh 2021, p. 15). Within this, the meanings of mixedness and the borders (both state and cultural/racial) which that they cross are revealed through the lived experiences and social interactions of mixed-race Asians both in Asia (Rocha and Fozdar 2019;Törngren and Sato 2021;Kimura 2020) and in the west (Williams-Leon and Nakashima 2001).…”
Section: Why Wasian?mentioning
confidence: 99%
“…before transitioning into 'Sweet Caroline' the focus shifts to 'white' objects or white ethnic objects (again with a The way that wasians think of themselves and how others perceive them may not be the same. The process of defining what it means to be 'wasian' and how we might identify that both interpersonally but also publicly (even on social media) involves a negotiation that goes on within the gap between those notions (Törngren and Sato 2021). In the first half of the sound 'wasian check' during the Asian 'traditional' sounding music, the focus is clearly on the Asian side of the family, culture and symbols that can convey just how authentically 'Asian' the wasian content creator actually is.…”
Section: Sound "Wasian Check" By Avaxwilkinsonmentioning
confidence: 99%
“…In some cases, they may experience an 'identity mismatch' between their self-identification and their ascribed or externally assigned identification (e.g. Daniel and Newman 2015;Franco, Katz, and O'Brien 2016;Roth 2016;Song 2017a;Song and Aspinall 2012;Tutwiler 2016; see also contributions by Chito Childs, Lyons, and Jones 2019;King-O'Riain 2019;Osanami Törngren and Sato 2019;Rodríguez-García et al 2019;Song 2019, in this volume).…”
Section: Scope and Objectives Of The Volumementioning
confidence: 99%
“…Specifically, mixed persons' identification(s) will be affected by different racialisation processes and policies that derive from the dominant racial ideologies of the state, such as anti-racialism, colour-blindness or multiculturalism on the one hand, and xenophobia, Islamophobia, colourism (Walker 1983), racism and antiblackness on the otheror the intersections of some of these systems. Moreover, the country's migration history (which will affect whether multigenerational minority populations exist), the colonialist history, existing transnational ties, diversity policies, social hierarchies and social attitudes also influence where mixed people are positioned in a society and what their choices are (see, for example, Chito Childs, Lyons, and Jones 2019;Osanami Törngren and Sato 2019;Rodríguez-García et al 2019, in this volume). In this way, it is clear that the meanings attached to phenotype, as well as to many other individual factors, are socially constructed and vary according to context.…”
Section: A Conceptual Model Of Mixednessmentioning
confidence: 99%